Fulfillment of Wife's Rights after Divorce in the Perspective of Legal Justice Theory and Maqashid Shari’ah Cum-Mubadalah - Usthyawati, Nur Ushmi; Muhaimin, Muhaimin; Satriya, Bangkit Budi (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The fulfillment of a wife's rights in contested divorce cases, including mut'ah, iddah alimony, and madliyah alimony, has historically lacked specific regulation, often resulting in injustice for women who initiate divorce. Divorce is not always the wife's choice; it may be influenced by factors such as discrimination or domestic violence, necessitating a legal review grounded in both maqashid shari’ah cum-mubadalah and legal justice theory. This study employs a normative-legal approach, analyzing conceptual and statutory legal materials. The findings reveal that the fulfillment of a wife's rights in contested divorce cases aligns with the principles of maqashid shari’ah, encompassing its five core objectives, while the cum-mubadalah principle emphasizes gender equality and justice comparable to rights in talak divorce. The study further demonstrates that fulfilling these rights considers women’s biological and social realities and adheres to Gustav Radbruch's legal justice theory by upholding justice, utility, and legal certainty. Practically, the research shows that basic wife’s rights, traditionally granted only in talak divorce, can and should also be recognized in divorce initiated by the wife, promoting equitable treatment and advancing gender justice within Islamic law. These findings contribute to both theoretical discourse and legal practice by integrating maqashid shari’ah, mubadalah, and legal justice theory, offering a normative framework for ensuring fairness in divorce litigation. The study also underscores the need for empirical research to complement the normative analysis and further strengthen legal policy and judicial practice.